Efektivitas dan Kontribusi Pajak Hotel dan Pajak Restoran Terhadap Penerimaan Pendapatan Asli Daerah (PAD) Kabupaten Jember - Ebtisam Lukman Basyarahil; Ririn Irmadariyani (UPT Penerbitan Universitas Jember, 2019)
This study aims to determine the effectiveness and contribution of hotel tax and restaurant tax on Revenue of Original Region of Jember Regency. The data that used in this research is secondary data which are a data of target and realization of Jember Regency Revenue of Original Region, hotel tax and restaurant tax from year 2011 to 2015. The analysis method used was descriptive quantitative. The results showed that the effectiveness of hotel tax and restaurant tax of Jember Regency during 2011 to 2015 in very effective category because the effectiveness level is above 100%. This indicates that the local government of Jember Regency has succeeded in achieving the target of hotel tax and restaurant tax which has been determined. While the contribution of hotel tax in 2011 to 2015 counted small to the Revenue of Original Region Jember Regency because the percentage of contribution per year is less than 20%. Likewise, the contribution of restaurant tax during 2011 to 2015 is small on the Revenue of Original Region Jember Regency. This means that the proportion of hotel taxes as well as small restaurant taxes on the revenue of PAD Kabupaten Jember. Keywords: Effectiveness, Contribution, Hotel Tax, Restaurant Tax, Revenue of Original Region.